Radioprotective effect of natural anthocyanins - Rożej, Adam; Małkowski, Bogdan; Andryskowski, Grzegorz; Niedworok, Jan; Grześków, Jerzy; Tryniszewski, Wiesław; Maziarz, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2000)
Aim : The effect of dye and black-fruit aronia juice on biochemical and morphological parameters in experimental animals exposed to a dose of 1,05 and 4,0 Gy gamma radiation was studied. Material and methods : The study was performed on 77 Chinchilla rabbits 2,5–3,2 kg body mass and 76 Balb C mice 18,0–21,5 g body mass. Blood was collected from rabbits marginal aural vein 48 h prior to irradiation and then 48 h and on 4 th and 10 th day after irradiation. In rabbits the leukocytes count and superoxide radical generation stimulated by peripheral blood granulocytes were investigated. In irradiated mice splenocytes chemiluminescence was examined on 3 rd day. Results : Statistically significant increase of superoxide radical generation was observed on the 4 th day after exposure to 1,05 Gy and after 48 h and on the 4 th day after exposure to a dose of 4 Gy of gamma radiation. Administration of anthocyanin dye inhibits significanthy superoxide radical generation on the 4 th day after exposure to the radiation dose of 4 Gy. On the 3 rd day after exposure to 4 Gy of gamma radiation both anthocyanin dye and concentrated juice increase the splenocytes chemiluminescence. Administration of natural anthocyanin dye to irradiated animals improves leukocytes count. Conclusion : * after exposure to gamma radiation dose the following was observed in irradiated animals: 1) increase of mean leukocyte count after exposure to a dose 1,05 Gy, 2) decrease of mean leukocyte count after exposure to a dose 4,0 Gy, 3) increase of superoxide radical, 4) decrease of splenocytes chemiluminescence, * administration of anthocyanin dye to animals exposed to gamma radiation dose of 4 Gy evokes: 1) decrease of superoxide radical generation, 2) increase of splenocytes chemiluminescence, * administration of anthocyanin dye to animals exposed to gamma radiation dose of 1,05 Gy produces leukocytes count normalisation.